Micropropagation of an endangered orchid Anoectochilus formosanus - Nguyễn, Văn Kết (Institute of Experimental Botany, Czech Academy of Sciences, 2022)
A rapid and efficient procedure is outlined for in vitro clonal propagation of an elite cultivar of jewel orchid (Anoectochilus formosanus). Multiple shoot proliferation was induced in shoot tip explants on Hyponex (H3) media supplemented with 1 mg dm-3 benzyladenine or 1 - 2 mg dm-3 thidiazuron (TDZ). Addition of activated charcoal (1 g dm-3) to the TDZ containing medium promoted multiple shoot formation (11.1 shoots per explant). However, the regenerated shoots had slow growth rate and failed to elongate. This problem was overcome by transferring the shoot clumps to a hormone free H3 medium supplemented with 2 % sucrose and 0.5 g dm-3 activated charcoal. Rooting was induced in 100 % of the regenerated shoots in the same media. The plantlets were acclimatized and established in greenhouse.